Structured Literature Reviews (SLR) of Urban Farming for Improving Economic Status of Urban Residents - Siti Aisyah Salim, Siti Hajar Salim, Fadhlina Mohd Razali (International Journal of Sustainable Construction Engineering and Technology, 2022)
The increasing of urban population demands the development of new technologies that provide sustainable living. This issue might debilitate the quality life of urban residents though city life always associated with national economic growth engine and social progress. Many initiatives have been commenced in elevating the economic status of urban residents including urban farming activities. In Malaysia, several stakeholders have pushed the potential of urban farming activities that help to create job, increase income, and serve as an urban garbage sink. Nonetheless, research that investigated urban farming activities could improve the economic status of urban residents still very lacking. Thus, this research aims to explore potential urban farming activities through structured literature reviews (SLR). It searched all the selected databases and found 851 papers: 378 from ScienceDirect, 17 from Web of Science and 456 from Scopus. These databases comprised comprehensive literature that concentrate on urban farming activities in Southeast Asia. Subsequently, the process of filtering was achieved based on intelligent processes. The process consists of three iterations of filtering, excluding duplicate articles, filtering titles and abstracts and reading full text articles. About 90 articles has been derived for the final classification of urban farming sub-topics. The details of the key features of topics will be discussed in the research which include the following aspects: the motivation towards urban farming activities, the advantages of urban farming especially for increasing the economic status of urban residents. The finding from this research could be used for future researchers to understand several sub-topics that related with urban farming urban residents that remain unexplored.